A Constraint Programming model for fast optimal stowage of container vessel bays - Delgado, Alberto; Jensen, Rune Møller; Janstrup, Kira; Rose, Trine Høyer; Andersen, Kent Høj (European journal of operational research, 2012)
► We study the container stowage problem within subsections of container vessel bays. ► A representative model of the problem is introduced. ► Integer and Constraint Programming approaches to solve these problems are compared. ► We do extensive testing with instances derived from real stowage plans. ► Our test instances are solved as required for application by the industry. Container vessel stowage planning is a hard combinatorial optimization problem with both high economic and environmental impact. We have developed an approach that often is able to generate near-optimal plans for large container vessels within a few minutes. It decomposes the problem into a master planning phase that distributes the containers to bay sections and a slot planning phase that assigns containers of each bay section to slots. In this paper, we focus on the slot planning phase of this approach and present a Constraint Programming and Integer Programming model for stowing a set of containers in a single bay section. This so-called slot planning problem is NP-hard and often involves stowing several hundred containers. Using state-of-the-art constraint solvers and modeling techniques, however, we were able to solve 90% of 236 real instances from our industrial collaborator to optimality within 1second. Thus, somewhat to our surprise, it is possible to solve most of these problems optimally within the time required for practical application.